Observations of flow distributions on wide wing-wall abutment in two-stage channel - Kenny (2018)
Scouring around abutment is a detrimental process to the structure foundation in which it causes the sediment bed to be undermined, making the foundation being shallower than it was designed and eventually leading to structural failure. Hence, emphasizing on the importance of being able to predict the ﬂow in scouring process around the structure. The objective of this study is to investigate the ﬂow ﬁeld around a wide 45◦ wing-wall abutment in the equilibrium scour hole condition under clear water condition. The ﬂow ﬁeld measurements were done by using an Acoustic Doppler Velocimeter (ADV). The experiment was conducted with a 80 cm wide wing-wall abutment situated in the ﬂoodplain sand bed of a 19 m long and 1.6 m wide two-stage channel ﬂume. In the equilibrium state, it was observed that there were 2 scour holes and 1 deposition ridge formed around the abutment. Equilibrium state of the sediment bed was frozen to reduce disturbance on the geometry during ﬂow measurements. The results of the ﬂow ﬁeld in terms of the velocity vectors and contours of turbulent intensities, turbulent kinetic energy and the Reynold shear stress in the scour hole are presented. The Reynold shear stress, turbulent intensities and turbulent kinetic energy share similar contour trend. In the sections where scour hole is shallow, the 3 components contours show an increase in value closer to the abutment. On the other hand, at section where scour hole is the deepest, high value of the 3 components are observed on the region between ridge at the end of scour hole.